Effect of cytochalasin B during oocyte maturation for parthenogenetic embryos generation in goat - RANJAN, R; DAS, B C; BAG, SADHAN (The Indian Journal of Animal Sciences, 2014)
The present experiment was conducted to study the effect of cytochalasin B (CCB) in maturation medium for parthenogenetic embryos generation in caprine (Capra hircus). The cumulus oocyte complexes (COC) were isolated, evaluated, graded and matured in maturation medium having different concentration of CCB (0 μg/ml, 5 μg/ml, 10 μg/ml, 15 μg/ml and 20 μg/ml). Matured oocytes were activated by 7% ethanol for 5 min followed by incubation with 2mM 6-dimethyl amino purine (DMAP) for 4 h and cultured in modified synthetic oviductal fluid (mSOF) in CO2 incubator at 37°C, 5% CO2, and 95% relative humidity. The cleavage rate and further embryo development was recorded after 48 h and then 96 h of in vitro culture. The overall oocyte recovery rate was 1.13±0.02/ovary. The overall cleavage rate was 77.22±1.04 and percentage of 2–4 cell, 8–16 and morula stage embryos production were 22.90±1.38, 34.46±0.89 and 42.64±1.04, respectively irrespective of different concentration of CCB used in maturation medium. There was nonsignificant difference of cleavage rate among different concentration of CCB used. The embryos development beyond 16 cell stage was higher in 15 μg/ml CCB compared to other concentration of CCB but nonsignificant compared to control (0 μg/ml CCB). The presence of CCB all throughout maturation (27 h) did not inhibit cleavage rate as well as embryo development, rather increased the embryo development beyond 16 cell stage.